Access to and utilization of health care services among Canada's immigrants. Issue 2 (13th June 2016) - Tiagi, Raaj
Abstract : Purpose: – The purpose of this paper is to analyze patterns of health services utilization – visits to family practitioner and visits to an emergency room – by recent immigrants (those who have lived in Canada for less than ten years) and "established" immigrants (those who have resided in Canada for ten years or longer) relative to their Canadian-born counterparts. Design/methodology/approach: – The 2009/2010 files of the Canadian Community Health Survey were used for the analysis. A logit model was used to analyze utilization while a zero-inflated negative binomial model was used to measure the intensity of health services utilization. Findings: – Results suggest that relative to native-born Canadians, recent immigrants are more likely to visit an emergency room and are less likely to visit a family/general practitioner. The opposite effect is observed for "established" immigrants. In terms of intensity of use, native-born Canadians are more likely to use physicians' services intensively compared with either recent or established immigrants. Originality/value: – The paper's findings suggest that provincial governments in Canada will need to focus effort to ensure that recent immigrants have access to a family/general practitioner. This will be necessary given the recent primary care reform initiatives introduced across Canada that emphasize the physician as the first point-of-contact with the health system.